2022
DOI: 10.1038/s41598-022-08734-8
|View full text |Cite
|
Sign up to set email alerts
|

An innovative method for soil vapor extraction to improve extraction and tail gas treatment efficiency

Abstract: This study aims to improve soil vapor extraction (SVE) to address its shortcomings in treating halogenated hydrocarbon-contaminated soil. Indoor simulation experiments based on SVE were conducted to provide technical guidance for the remediation of 1,2-DCA-contaminated soil, with the overall intention of soil repair and ecological restoration. A thermal oxidation SVE (TOSVE) system was designed on the basis of SVE technology for application in the remediation of low-permeability soil contaminated with halogena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…For instance, the results of indoor soil column tests by Yin et al [17] showed that the SVE technology can reduce the concentration of multicomponent VOCs in soil columns by up to 99.52%. Nevertheless, when SVE technology is applied in the field compared to indoor test results, its efficiency in removing VOCs can be greatly reduced due to limitations such as large site areas and poor permeability of contaminated soil [18]. Labianca et al [19] reported from field tests that after four years of SVE treatment, the concentration of VOCs in organic pollution sites was reduced by only 73%, which is lower than the results observed by Yin et al [17].…”
Section: Introductionmentioning
confidence: 88%
“…For instance, the results of indoor soil column tests by Yin et al [17] showed that the SVE technology can reduce the concentration of multicomponent VOCs in soil columns by up to 99.52%. Nevertheless, when SVE technology is applied in the field compared to indoor test results, its efficiency in removing VOCs can be greatly reduced due to limitations such as large site areas and poor permeability of contaminated soil [18]. Labianca et al [19] reported from field tests that after four years of SVE treatment, the concentration of VOCs in organic pollution sites was reduced by only 73%, which is lower than the results observed by Yin et al [17].…”
Section: Introductionmentioning
confidence: 88%
“…Generally, the higher the gas temperature, the higher the saturation vapour pressure of the contaminants, displaying properties similar to water. This makes it more favourable for contaminants to transfer to the gas phase and be removed [10,39]. This indicates that when considering the capability of CW laser remediation for soils with different pore structures, the magnitude of the Nusselt number from the perspective of gas temperature is a determining factor.…”
Section: Simulation Predictionmentioning
confidence: 99%
“…In order to reduce the number and scale of experiments, the use of numerical simulations to analyze and predict the SVE process before formal testing has become an important way to develop SVE technology [14,15]. Numerical models can assist in the setting of soil parameters [16,17] and process flow design in SVE systems [18,19], as well as in the evaluation of the duration and effectiveness of SVE [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In order to reduce the number and scale of experiments, the use o ical simulations to analyze and predict the SVE process before formal testing has an important way to develop SVE technology [14,15]. Numerical models can ass setting of soil parameters [16,17] and process flow design in SVE systems [18,19] as in the evaluation of the duration and effectiveness of SVE [20][21][22]. While soil parameters and process flow are important, the final evaluation al to consider the performance parameters of the equipment, which will affect whe equipment performs fully or whether it can achieve the VOC removal rate and required to complete the cleanup target as assessed by theoretical calculations a tests, which is important for government departments and project operators to before investing in the project [23].…”
Section: Introductionmentioning
confidence: 99%